A contribution to the systematics of the genus Manota Williston (Diptera: Mycetophilidae) in Brazil - Kurina, Olavi; Hippa, Heikki; Amorim, Dalton De Souza (Zootaxa, 2018)
A total of 286 male specimens of Manota from 38 different collecting sites in the Brazilian Atlantic Forest were analysed. They belong to 32 different species, including 20 described as new to science and 12 recognized as previously described species. The new species are M. abbreviata sp. n., M. atlantica sp. n., M. carioca sp. n., M. cavata sp. n., M. hirta sp. n., M. lamasi sp. n., M. lanei sp. n., M. nordestina sp. n., M. oliveirai sp. n., M. paniculata sp. n., M. papaveroi sp. n., M. periotoi sp. n., M. perparva sp. n., M. pseudoiota sp. n., M. rostrata sp. n., M. sanctavirginae sp. n., M. securiculata sp.n., M. silvai sp. n., M. tavaresi sp. n. and M. unispinata sp. n. The taxonomic context of the newly described species is discussed. Manota palpalis Lane, 1948, the type of which is considered lost, is redescribed and discussed, based on the original description, the original illustrations, and the type-locality. Our specimens of the previously described species belong to M. aligera Hippa, Kurina & Sääksjärvi, 2017, M. anfracta Hippa & Kurina, 2013, M. appendiculata Hippa & Kurina, 2013, M. caribica Jaschhof & Hippa, 2005, M. diversiseta Jaschhof & Hippa, 2005, M. micula Hippa & Kurina, 2013, M. panda Hippa & Kurina, 2013, M. pustulosa Hippa, Kurina & Sääksjärvi, 2017, M. quantula Hippa & Kurina, 2013, M. serrulata Hippa, Kurina & Sääksjärvi, 2017 and M. subaristata Kurina, Hippa & Amorim, 2017. Among the species dealt with here, ten have a wide distribution in South America or the Neotropics, six are known from only a single site, nine are widespread along the Atlantic Forest, and seven are known only from southern Brazil/northwestern Argentina. A discrepancy between the distribution patterns of Manota species and the general areas of endemism known for flies in the Atlantic Forest is discussed, and a non-destructive sequencing reverse workflow protocol for Manota specimens proposed.        Including the species described here, the Neotropical region closely approaches the Oriental region in terms of the number of described species (92 and 102, respectively), while the genus now includes 300 species worldwide.